2022
DOI: 10.3389/fagro.2022.869770
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genomic Regions Govern Tolerance to Sulfentrazone in Snap Bean (Phaseolus Vulgaris L.)

Abstract: The availability of effective weed management tools against waterhemp (Amaranthus tuberculatus) is crucial to maintain profitable production of snap bean (Phaseolus vulgaris L.). Preemergence herbicides enable the crop to gain a size advantage over the weed, but the few preemergence herbicides registered in snap bean have poor control of waterhemp. Sulfentrazone, a protoporphyrinogen oxidase (PPO) -inhibiting herbicide, provides significant control of waterhemp and other problematic weeds. However, crop tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…They differ in several traits including growth habit (i.e., bush and pole), market type (i.e., fresh and processing), pod sieve class (i.e., two to six, and flat), and seed size (i.e., 8 to 58 g per 100-seed). Cultivars used in the present work are a subset ( n = 277) of the SNAP panel that also was tested for tolerance to sulfentrazone (Saballos et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They differ in several traits including growth habit (i.e., bush and pole), market type (i.e., fresh and processing), pod sieve class (i.e., two to six, and flat), and seed size (i.e., 8 to 58 g per 100-seed). Cultivars used in the present work are a subset ( n = 277) of the SNAP panel that also was tested for tolerance to sulfentrazone (Saballos et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…diversity panel ( n > 120) confirmed that several herbicides used in grain-type soybean were just as safe on edamame grown throughout the United States, facilitating herbicide registrations on the minor crop (Williams and Nelson 2014). Moreover, evaluating herbicide tolerance in a diversity panel with associated genomic data may identify genomic regions related to herbicide tolerance, which could be useful in crop improvement (Saballos et al 2022). Therefore, the objective of this research was to quantify the extent to which pyroxasulfone tolerance exists in a diverse snap bean panel.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs with 40% or more missing values were eliminated. The methods of alignment and imputation are otherwise identical to those described by Saballos et al (2022) [ 25 ]. Because the SBDP is a subpopulation of the SnAP, a subset of the GBS data extracted from the original resource (SnAP) was used for all association studies using the SBDP.…”
Section: Methodsmentioning
confidence: 99%
“…The panel includes accessions with determinate bush (CIAT classification type I) growth habits, but a few were half-runners (type III), and another subset had an indeterminate (type IV) climbing growth habit. The accessions represent different market classes, such as Blue Lake, European small sieves, Refugee and Romano beans, and yellow (wax) beans of American or European origin [23].…”
Section: Plant Materialsmentioning
confidence: 99%
“…HapMap files of the SnAP aligned to the two reference genomes were produced by Alvaro Soler Garzon of the Miklas Lab, USDA-ARS, Prosser, WA. Alignment and imputation methods are described by Saballos et al [23]. After 0.01 minor allele frequency (MAF) filtering, 25,472 SNPs were generated with G19833 (v2.1), and 34,442 SNPs were generated with 5-593 (v1.1) reference genomes.…”
Section: Data Acquisitionmentioning
confidence: 99%